Fréchet subdifferential calculus and optimality conditions in nondifferentiable programming - Mordukhovich, B. S.; Nam, N. M.; Yen, N. D. (Optimization, 2006)
We develop various (exact) calculus rules for Fréchet lower and upper subgradients of extended-real-valued functions in real Banach spaces. Then we apply this calculus to derive new necessary optimality conditions for some remarkable classes of problems in constrained optimization including minimization problems for difference-type functions under geometric and operator constraints as well as subdifferential optimality conditions for the so-called weak sharp minima. §Dedicated to Diethard Pallaschke in honor of his 65th birthday.